Onsite Sewage Treatment and Disposal Systems: An Overview - Gurpal S. Toor; Mary Lusk; Tom Obreza (EDIS)
This 7-page fact sheet introduces common types of septic systems and briefly discusses onsite wastewater flow and the contaminants found in wastewater. Written by Gurpal Toor, Mary Lusk, and Tom Obreza, and published by the UF Department of Soil and Water Science, June 2011.